Relationship between socio-economic factors and participation in decision making in microfinance scheme among rural farmers in Kano, Nigeria - Saidu, Mohammed Bashir; Abu Samah, Asnarulkhadi; Redzuan, Ma'rof; Ahmad, Nobaya (Marsland Press, 2014)
This study examined the relationships between socio-economic factors and participation in decision making among rural farmers in Kano, Nigeria. Data was collected from 364 respondents using structured questionnaire from six local government areas of Kano state. The descriptive analysis revealed that there is high level of participation in decision making among rural farmers community in Kano based on the overall mean score of 4.19 and standard deviation of 0.81. Spearman Rho correlation analysis also shown significant negative relationship between level of education and participation in decision making (rs = -.372, p = .000) which means, majority of people in the study areas are not educated since some of them who acquired educational qualifications look for better job opportunities instead of participating in agricultural activities. Therefore, the authors recommended that, government should either increase the amount of microloan uniformly or give special consideration to educated people in order to curtail rural-urban migration for ‘white collar’ jobs. Similarly, the analysis shown that, there is significant positive low relationship between type of farm product and participation in decision making (rs = .184, p = .001), which means, people involvement in rural development program has low impact on their agricultural production. Thus, the authors recommends that, government should give more financial support to rural farmers in order to increase their capital base to enhance agricultural production in the study areas which may eventually lead to improvement in well-being of the farming communities.